Chinese, Tusan and Kuei: the representation or chinese peruvian identity in Siu Kam Wen’s short stories - Paoliello (The University of Edinburgh), Antonio (ANTARES: Letras e Humanidades, 2013)
This article explores the ways in which Chinese Peruvian writer Siu Kam Wen portrays Chinese identity in the short stories contained in El Tramo final (The Final Stretch). Siu Kam Wen is considered one of the most important authors of the Generation of 1980 and the collection analysed in the present article represents a milestone in Peruvian literature. Published in Lima in 1985, El tramo final is the first work by a Peruvian narrator of ethnic Chinese background to depict the Chinese Peruvian experience from within. Through this article, I aim at investigating how the short stories by Siu help us understand the specificity of Chinese Peruvian life, especially in Lima's Chinese Quarter, and to what extent they invigorate and/or refute the ideas on ethnic Chinese people that prevail in mainstream Peruvian society.